Toponimi Pedukuhan di Kelurahan Panggungharjo Bantul Yogyakarta dan Implikasinya dalam Konteks Budaya - Ayu Safitri; Ni Gusti Ayu Roselani (Pusat Riset dan Inovasi Nasional, 2024)
This study examines the toponymy of hamlets in Panggungharjo village located in Bantul district, Yogyakarta. This study aims to understand the meaning, origin of the names of hamlets in Panggungharjo village, their morphological processes and their implications in the context of local culture. Using qualitative methods, this study collected data through interviews with community leaders and through existing literature reviews. This study also does not exclude information from the official village website. This study found that the naming of hamlets in Panggungharjo village showed the influence of reflection of the manifestation aspect found in five hamlets and the societal aspect found in nine hamlets. This study also found morphological processes that occurred in the toponymy of hamlets in Panggungharjo village, namely affixation, repetition (reduplication), compounding, abbreviation (acronym), and changes in sounds, both vowels and consonants. The results of this study indicate that there is a relationship between culture and naming, namely culture is one of the factors influencing the naming of hamlets in Panggungaharjo sub-district.